Efficacy of Abelmoschus esculentus (Okra) Seeds, Tamarindus indica (Tamarind) Seeds and Zea mays (Corn) Husk as an Alternative to Chemical Based Coagulants and Flocculants in Treating Waste Water - Baugbog, Victoria Janelle V. (Animo Repository, 2022)
The chemical coagulants used for treating the wastewater are associated with non-biodegradability resulting in health implications due to inadequate water quality standards. Thus, the study was conducted to assess the efficacy of Abelmoschus esculentus (okra) seeds, Tamarindus indica (tamarind) seeds, and Zea mays (corn) husk as an alternative biocoagulant and bioflocculant to chemical coagulants in treating wastewater. An experimental research design was employed wherein nine experimental groups with varying dosages and mixing speeds were evaluated regarding their relationship and difference against three treatments of Aluminum sulfate. Turbidity, Total Dissolved Solids (TDS), and pH level were water quality parameters assessed in the study wherein the coagulation-flocculation process was evaluated to treat the wastewater. Results showed that 800 mg/L at 175 RPM - 200 RPM natural treatment produces the lowest mean TDS value and produces the highest pH value. Using Two-Way ANOVA, the computed F Crit-values were 3.555 for the difference and 2.928 for the interaction. The dosage observed significant differences with regards to the observed water quality parameters, the mixing speed observed a significant difference in terms of pH, and the interaction between dosage and mixing speed showed a significant relationship regarding TDS. Using One-Way ANOVA, the computed F Crit-values were 2.18. There were significant differences found in terms of all the observed water quality parameters. In conclusion, the natural treatments are found to be effective in treating wastewater against Aluminum sulfate. Future researchers are recommended to increase parameters for testing such as Dissolved Oxygen and Total Solids.